Carbon disclosure, stock returns, institutional investors and the nature of corporate equity: An empirical study of Chinese market based on fixed effects model - jinyu, Wu (2022)
Changes in the environment and climate have prompted countries to issue relevant policies to curb greenhouse gas emissions. Carbon disclosure policy is one of them. Carbon disclosure refers to the fact that the subject of greenhouse gas emissions can provide real and comprehensive carbon emission information in the form of regular reports or ad hoc reports. A behavior of social opening, as the main body of the market, the carbon disclosure of enterprises will have a certain impact on the capital market, and the behavior of investors may also change. The objective of this paper is to explore the impact of carbon disclosure on China's capital markets and investor behavior. The targets are as follows: 1. Relationship between stock yields and carbon disclosure. 2. The relationship between institutional investor shareholding ratio and carbon disclosure and stock return 3. What impact does institutional investment shareholding have on the relationship between carbon disclosure and stock return4. Due to the large number of state-owned enterprises in China's carbon emissions market, the paper also studies the impact of corporate nature on the relationship between carbon disclosure and stock returns This paper selects 100 listed companies from the sample stocks of the Shanghai 180 Carbon Efficiency Stock Exchange in China as a sample and selects relevant financial data of these companies for a total of five years from 2016-2020 2 for analysis. Then establish carbon disclosure assessment system to digitize the quality of carbon disclosure of enterprises. The next step in this paper is to use a fixed effect model to conduct regression analysis to test the hypothesis. According to the results, carbon disclosure is significantly positively correlated with stock returns. But institutional investor ownership does not significantly affect carbon disclosures or stock returns. The positive relationship between carbon disclosure and stock returns can be strengthened by the number of institutional investors. Lastly, this paper concludes that stock returns are more sensitive to changes in carbon disclosure in private firms than in state firms by aggregating firms in the sample into state and private firms. The conclusions of this paper can provide reference for some stakeholders; the government can better promote the implementation of corporate carbon disclosure policies; and investors in the market can also use some of the conclusions of this paper as a reference for investment portfolios. However, there are also shortcomings in this paper, such as the small number of sample data and the strong subjectivity of carbon disclosure indicators, which need to be improved.